36. NEWBORN OUTCOMES IN PREGNANT WOMEN OF PREMATURE RUPTURE OF MEMBRANES AT HANOI OBSTETRICS AND GYNECOLOGY HOSPITAL (Vietnam Journal of Community Medicine, 2024)
Objective: Evaluate pregnancy outcomes of pregnant women with premature rupture of membranes at gestational age from 24 to 34 weeks at Hanoi Obstetrics and Gynecology Hospital. Subjects and methods: A retrospective cross-sectional descriptive study on 217 pregnant women with preterm rupture of membranes at gestational age from 24 weeks 0 day to 33 weeks 6 days at Hanoi Obstetrics and Gynecology Hospital from January 2022 to December 2022. Results: The average age of pregnant women was 30.1±6.1. Premature rupture of membranes is common in pregnant women with a history of previous cesarean section (33.2%), history of abortion (20.7%), and miscarriage and stillbirth (15.6%). Fetuses weighing from 1500 to 2500g account for the highest proportion (70.5%). 100% of children weighed
Keywords: Premature rupture of membranes, neonatal outcome.